Harnessing the IL-7/IL-7Rα axis to improve tumor immunotherapy. (3rd May 2016) - Johnson, C. Bryce; Wrangle, John; Mehrotra, Shikhar; Li, Zihai; Paulos, Chrystal M.; Cole, David J.; Surh, Charles D.; Rubinstein, Mark P.
ABSTRACT: IL-7 and IL-15 are critical for supporting T cells transferred into a lymphopenic environment. As activated CD8 + T cells downregulate IL-7Rα, it is thought IL-15 is more important. However, we find that CD8 + T cells activated with IL-12 have elevated IL-7Rα and rely on IL-7 for persistence and antitumor immunity.